Heterogeneity in the associations between common mental disorders and labour outcomes - a population study from southern Sweden - Johan Jarl; Anna Linder; Hillevi Busch; Anja Nyberg; Ulf-G Gerdtham (BMC, 2020)
Abstract Background Previous research has shown that Common Mental Disorders (CMD) are unequally distributed between population subgroups, but we know less about how labour outcomes following such disorders are distributed. Our aim is to investigate how the labour outcomes following a CMD diagnosis differ over sex, age, schooling and country of birth. Methods We use a population sample from southern Sweden of patients diagnosed with CMD during calendar years 2009-2011, and a matched general population control group, to study labour market outcomes three years following diagnosis. Logistic regression is used to study the associations between a CMD diagnosis and outcomes in employment, sick leave, and disability pension. Interaction analysis is used to study heterogeneity in these associations. Results CMD diagnosis is associated with reduced employment and increased odds of sick leave and disability pension. Following a CMD diagnosis, men and higher educated individuals have higher odds of non-employment and sick leave compared to women and the lower educated. Foreign-born individuals have higher odds of non-employment and lower odds of sick leave, compared to individuals born in Sweden. Heterogeneity appears to be present also based on age. Younger age is associated with higher odds of non-employment and disability pension and lower odds of sick leave, following a CMD diagnosis. Conclusions Heterogeneity in labour outcomes following a CMD diagnosis sometimes contributes to and sometimes mitigates inequalities in employment, sick leave and disability pension between population subgroups. When developing new strategies to tackle mental ill-health in the population, it may therefore be motivated to consider not only inequalities in the prevalence of mental disorders but also heterogeneity in associated adverse labour outcomes.